Penyuluhan Hukum Tentang Perlindungan Konsumen Pada Transaksi Jual Beli Online Di Kelurahan Palabusa Kecamatan Lea-Lea Kota Baubau - Ernawati Ernawati; rizki mustika suhartono; Gurusi Gurusi; La Ode Muhammad Karim; Muhamad Irwan Sugianto; Risaldi Risaldi (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to provide knowledge and understanding of buying and selling to the people of Palabusa Village. The method used in carrying out activities is counseling and question and answer. The results and discussion, namely Community Service is legal counseling involving Law Faculty Lecturers and Amaliah Work College Students (KKA) to provide legal counseling before the Palabusa Village community. Legal education about buying and selling is very much needed for the community, considering buying and selling is an act that is often carried out in everyday life.